Potent chitin-hydrolyzing enzyme from Myrothecium verrucaria affects growth and development of Helicoverpa armigera and plant fungal pathogens - Vidhate, Ravindra P.; Bhide, Amey J.; Gaikwad, Sushama M.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2019)
Chitin, a crucial structural and functional component of insects and fungi, serves as a target for pest management by utilizing novel chitinases. Here, we report the biocontrol potential of recombinant Myrothecium verrucaria endochitinase (rMvEChi) against insect pest and fungal pathogens. A complete ORF of MvEChi (1185 bp) was cloned and heterologously expressed in Escherichia coli. Structure based sequence alignment of MvEChi revealed the presence of conserved domains SXGG and DXXDXDXE specific for GH-18 family, involved in substrate binding and catalysis, respectively. rMvEChi (46.6 kDa) showed optimum pH and temperature as 7.0 and 30 degrees C, respectively. Furthermore, rMvEChi remained stable within the pH range of 6.0 to 8.0 and up to 40 degrees C. rMvEChi exhibited k(cat)/K-m values of 129.83 x 10(3) [(g/L)(-1) s(-1)] towards 4MU chitotrioside. Hydrolysis of chitooligosaccharides with various degrees of polymerization (DP) using rMvEChi indicated the release of DP2 as main end product with order of reaction as DP6 > DP5 > DP4 > DP3. Bioassay of rMvEChi against Helicoverpa armigera displayed potent anti-feedant activity and induced mortality. In vitro antifungal activity against plant pathogenic fungi (Ustilago maydis and Bipolaris sorokiniana) exhibited significant inhibition of mycelium growth. These results suggest that MvEChi has significant potential in enzyme-based pest and pathogen management. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biocontrol; endochitinase; Myrothecium verrucaria

Genomic determinants of entomopathogenic fungi and their involvement in pathogenesis - Vidhate, Ravindra P.; Dawkar, Vishal V.; Punekar, Sachin A.; Giri, Ashok P. (Microbial Ecology, 2023)
Entomopathogenic fungi offer an effective and eco-friendly alternative to curb insect populations in biocontrol strategy. The evolutionary history of selected entomopathogenic fungi indicates their ancestral relationship with plant endophytes. During this host shifting, entomopathogenic fungi must have acquired multiple mechanisms, including a combination of various biomolecules that make them distinguishable from other fungi. In this review, we focus on understanding various biochemical and molecular mechanisms involved in entomopathogenesis. In particular, we attempt to explain the indispensable role of enlarged gene families of various virulent factors, viz. chitinases, proteases, lipases, specialized metabolites, and cytochrome P450, in entomopathogenesis. Our analysis suggests that entomopathogenic fungi recruit a different set of gene products during the progression of pathogenesis. Knowledge of these bio-molecular interactions between fungi and insect hosts will allow researchers to execute pointed efforts towards the development of improved entomopathogenic fungal strains.
Keywords: Biocontrol; Chitinases; Endophytic fungi; Entomopathogenic fungi; Hydrolytic enzymes; Insect pests